ANALYSIS OF THE IMPLEMENTATION OF STEM-BASED MODULES ON PERCEPTIONS OF TEACHER AND STUDENT READINESS DURING THE INDEPENDENT CURRICULUM PERIOD (a Case study at High School No. 2 Kesuma Bangsa) - Sarah, Cut; Alvina, Sirry; Imanda, Riska; Muliaman, Agus; Unaida, Ratna (Chimica Didactica Acta, 2024)
This research aims to determine the readiness of teachers and students in the implementation of STEM-based modules for class X SMA Negeri 2 Kesuma Bangsa in chemistry subjects. The type of research used is qualitative descriptive research. The population in This research is all class X students at SMA Negeri 2 Kesuma Bangsa, while the sampling technique in this research is saturated sampling. Study This will be implemented in the odd semester of the 2023/2024 academic year. Data collection techniques are in the form of interviews, observations, questionnaires, and documentation. Data analysis determines the level of teacher readiness and student learning readiness in following the chemistry learning process by implementing STEM-based modules and calculating percentage values. The questionnaire then describes the results of the interviews and observations that have been carried out. The results showed that the class X chemistry teacher at SMA Negeri 2 Kesuma Bangsa is ready to teach by obtaining an average score of 95.49, included in the very good category; this is proven by the results of the interviews showing that teachers are capable of developing curriculum and competency standards graduates, and development of learning tools. Class X students' learning readiness in SMA Negeri 2 Kesuma Bangsa obtained an average score of 81.12, included in the very good category. This is proven by observation results, showing that students are ready based on physical, psychological, and material readiness indicators. It can be concluded that the readiness of chemistry teachers and class X students of SMA Negeri 2 Kesuma Bangsa are ready to implement STEM-based modules.